Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1939-7445.2011.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Climate Change Impact on Loblolly Pine Plantations in the Southern United States

Abstract: Few studies have empirically examined climate change impacts on managed forests in the southern United States. In this paper, we use the U.S. Forest Service's Forest Inventory and Analysis Database to fit two growth models across the South and apply the four Hadley III climate scenarios developed for the Intergovernmental Panel on Climate Change Fourth Assessment Report to project future growth and site productivity on loblolly pine plantations. The static growth model provides a direct test of whether a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Huang et al. () predicted more growth in cooler parts of the region (upper Coastal Plain and Piedmont regions) and less in the warmer lower Coastal Plain, which was in good agreement with our results using many more climate projections and a different modeling approach. The two studies vary somewhat in the magnitude of the growth response but the trends and pattern of responses were very similar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Huang et al. () predicted more growth in cooler parts of the region (upper Coastal Plain and Piedmont regions) and less in the warmer lower Coastal Plain, which was in good agreement with our results using many more climate projections and a different modeling approach. The two studies vary somewhat in the magnitude of the growth response but the trends and pattern of responses were very similar.…”
Section: Discussionsupporting
confidence: 92%
“…An assessment of climate change effects on growth for the loblolly pine region was conducted by Huang, Abt, Kindermann, and Ghosh () using four Hadley III climate change scenarios from the IPCC's Fourth Assessment Report (IPCC ) and two stand‐level biometric growth models that incorporated maximum and minimum temperature and precipitation. Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of water stress is one of the most systemic stresses through the natural range of loblolly pine, with frequent periods of low rainfall and high A c c e p t e d M a n u s c r i p t 13 temperatures through the growing season (Huang, Abt, Kindermann, & Ghosh, 2011), leading to high vapor pressure deficits causing stomatal conductance to decrease (Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that increased temperatures could negatively affect forest productivity (Chmura et al, 2011) or have negligible effects at the regional level (Huang et al, 2011). McNulty, Vose, and Swank (1996) claimed that increases in temperatures between 2°C and 7°C could dramatically decrease net primary productivity of loblolly pine across the southern United States by as much as 60% (Florida) and as little as 15% (Virginia).…”
Section: Carbon Dioxide and Temperaturementioning
confidence: 99%